Community Health Agent knowledge and conduct towards first aid - Juliana Alice de Oliveira Ventorini; Márcio Rossato Badke; Silvana Bastos Cogo Bisogno; Susane Flôres Consentino; Vinicíus Ornel dos Santos (Universidade Federal de Santa Maria, 2012)
Objective: to verify the knowledge of Community Health Agents (CHA) in relation to first aid in a city located in northern Rio Grande do Sul, Brazil and identify the main urgent and emergency situations that they have witnessed in their work. Method: exploratory/descriptive qualitative study conducted in August 2010, through semi structured interviews, the results were analyzed using thematic analysis. Results: the participants were ten CHA selected by intentional sampling; seven reported having witnessed a first aid situation at their work. These respondents also reported having intervened in the incident, by at least in the act of calling for help. As for the actions of these seven in a cardiac arrest situation it was found that the participants believed that the victim would be dead due to lack of a pulse and respiration. Conclusion: the CHA are knowledgeable in emergency situations, but often insufficient, requiring greater knowledge